Disorders of Sex Development: A Review - Maharaj, Dushyant (Current Women's Health Reviews, 2008)
Disorders of sex development comprises a spectrum of embryological anomalies resulting in ambiguous genitalia at birth or develops at puberty ie., the appearance of the external genitalia being at variance with normal development for either sex. Sex outcome at birth is the result of a coordinated and sequential series of developmental events controlled by temporally expressed genes and hormones. The birth of an infant with ambiguous genitalia is one of the most difficult challenges faced by physicians. Management is compounded by psychological, social, ethical, and sexual concerns. Genetic issues dominate the pathophysiology of disorders of sex development, and in the long term management would include the skills of counselors trained in psychosexual issues affecting children and adolescents. The management of disorders of sex development is quite complex, and a multidisciplinary team network of appropriate professionals is essential. The decision of sex of rearing and the timing of surgery need careful consideration within a multidisciplinary environment with full informed consent of the family. This review gives an overview of disorders of sex development with emphasis on the more frequently encountered anomalies, the pathophysiology, presentation, and management.
Keywords: sex development